Circulating Th1, Th2, Th9, Th17, Th22, and Treg Levels in Aortic Dissection Patients. (6th September 2018) - Ye, Jing; Wang, Yuan; Wang, Zhen; Ji, Qingwei; Huang, Ying; Zeng, Tao; Hu, Haiying; Ye, Di; Wan, Jun; Lin, Yingzhong
Abstract : Background . Previous studies demonstrated that the subsets of CD4+ T helper (Th) cells are closely related to vascular diseases, including atherosclerosis and hypertension. This study is aimed at investigating the circulating Th1, Th2, Th9, Th17, Th22, and Treg levels in aortic dissection (AD) patients. Methods . Blood samples from AD (n = 56 ) and non-AD (NAD, n = 24 ) patients were collected, and the circulating levels of Th1, Th2, Th9, Th17, Th22, and Treg cells and their transcription factors and functional cytokines were measured by flow cytometric analysis, quantitative polymerase chain reaction, and enzyme-linked immunosorbent assays, respectively. In addition, the human aortic vascular smooth muscle cells (HASMCs) were treated with saline, angiotensin II (Ang II), or plasma from AD patients. Results . Compared with the levels in the NAD group, the Th1, Th9, Th17, Th22, and their transcription factor levels were increased and the Th2, Treg, and their transcription factor levels exhibited a decreasing trend in AD patients. In addition, higher IFN- γ, IL-9, IL-17, and IL-22 levels and lower IL-4 and IL-35 levels were observed in AD patients. Simple linear regression analysis and binary logistic regression analysis suggested that Th1/IFN- γ, IL-9, Th17/IL-17, and Th22/IL-22 positively regulated the occurrence of AD, while Th2/IL-4 and Treg/IL-35 negatively regulated the occurrence of AD. Plasma from AD patients further increased Bax mRNA levels but decreased Bcl2 and α -SMA mRNA levels in Ang II-treated HASMCs. Conclusions . Changes in Th1, Th2, Th9, Th17, Th22, and Treg activity are associated with the onset of AD. Different subsets of CD4+ T cells play different roles in the presence of AD.